Current Knowledge Regarding Long-Term Consequences of Pediatric Intensive Care: A Staff Survey in Intensive Care Units in German-Speaking Countries - Von Borell, Florian; Engel, Juliane; Neunhoeffer, Felix; Hoffmann, Florian; Michel, Jörg (Frontiers in Pediatrics, 2022)
Background: The Post Intensive Care Syndrome (PICS) describes new impairments of physical, cognitive, social, or mental health after critical illness. In recent years, prevention and therapy concepts have been developed. However, it is unclear whether and to what extent these concepts are known and implemented in hospitals in German-speaking countries. Methods: We conducted an anonymous online survey in German-speaking pediatric intensive care units on the current state of knowledge about the long-term consequences of intensive care treatment as well as about already established prevention and therapy measures. Results: We received 98 responses, 54% of the responses came from the nursing sector, 43% from the medical sector and 3% from the psychological sector. As a main result our survey demonstrated that for 25% of the respondents PICS had no importance in their daily clinical routine and. 8% stated to have a guideline on family-oriented treatment and 5% stated to have an implemented guideline for increasing patient comfort. The existence of a follow-up outpatient clinic was mentioned by 14% of the respondents. Frequent reported barriers to providing early mobilization and follow-up clinics were lack of time and staff. Core outcome parameters and feasible preventative measures were surveyed. Conclusion: The survey outlines the current state of knowledge, preventive measures, and therapies regarding Pediatric Post Intensive Care Syndrome in pediatric intensive care units in German-speaking countries. Overall, the concept of PICS seems to be underrepresented in German-speaking pediatric intensive care units. It is crucial to focus on long-term complications after pediatric critical care and to strive for further research to develop screening tools and treatment options and therewith ultimately improve long-term outcomes.